Autoarquivamento e representação de assunto: estudo analítico de teses e dissertações do Repositório Institucional da UFSCar - Freitas, Marina Penteado de (Universidade Federal de São Carlos, 2019)
There is a lack of research in the Information Science literature on self-archiving in institutional repositories, regarding the quality of representation of the documentary information and, consequently, the information retrieval capabilities. Investigations on the indexing practices of scientific production using self-archiving procedures are relevant on order to contribute to the improvement of quality both of information representation and of information retrieval by subject in institutional repositories. The research focus of this dissertation is on the lack of empirical investigation on the consequences of information retrieval in open access institutional repositories. Therefore, the aim is to investigate the self-archiving effects on the consistency in indexing by subject in institutional repositories focusing on the theses and dissertation collection. The empirical investigation concentrated on analyzing the results of unmediated self-archiving by authors/researchers compared to the same process executed by a librarian specialized in self-archiving. The evaluation centered on the dissertations and theses of the Science, Technology, and Society Postgraduate Programme available in the Institutional Repository of the Federal University of Sao Carlos (UFSCar). The aim is to contribute from a theoretical-methodological perspective to harmonize self-archiving practices and the consistency in indexing scientific production of the Brazilian institutional repositories. The secondary objectives are the following: a) contextualize the institutional repositories from the Information Science perspective emphasizing the modern practices of documentary information representation in a digital context; b) characterize self-archiving practices in both national and international institutional repositories; c) investigate the indexing consistency of theses and dissertations in the RI/UFSCar applying the intrinsic qualitative evaluation method. The investigation is exploratory and descriptive, applying the bibliographic research method to perform a qualitative analysis. The results show a similarity between the indexes evaluated, but the user’s indexation took more time and was less precise than the expert librarian’s indexation. A possible solution to deal with the lack of terms precision is to provide documentary languages to users/researchers as references for terms assignment, subject metadata validation by librarians, and indexing policies elaboration to improve representation and retrieval by subjects in institutional repositories.

La investigación dedicada al autoarchivo en repositorios institucionales es escasa en la literatura nacional e internacional de bibliotecas y ciencias de la información, específicamente sobre la calidad de la representación temática de la información y, en consecuencia, la posterior recuperación por materias en estos entornos digitales. Teniendo en cuenta lo anterior, el problema de la investigación se debe a la falta de estudios que investiguen las implicaciones del autoarchivo en la recuperación de sujetos en repositorios institucionales de acceso abierto. Por lo tanto, se propone investigar el impacto del autoarchivo en la consistencia de la indización de sujetos en repositorios institucionales con la recopilación de tesis y disertaciones como un recorte de investigación. Con este fin, la consistencia de la indexación libre realizada por el autor / investigador en el proceso de autoarchivo se compara con la de un bibliotecario que se especializa en el proceso de indexación de temas, con un enfoque de investigación centrado en la evaluación de la tesis del índice y la tesis. Institución institucional de la Universidad Federal de São Carlos defendida en el Programa de Postgrado en Ciencia, Tecnología y Sociedad e Ingeniería de Producción. En este sentido, buscamos contribuir con perspectivas teórico-metodológicas que proporcionen una consonancia entre la práctica del autoarchivo y la consistencia de la indexación de publicaciones científicas presentes en los repositorios institucionales brasileños, teniendo como objetivos específicos: a) contextualizar los repositorios institucionales desde la perspectiva de Información, con atención a las prácticas contemporáneas de representación temática de la información en el contexto digital; b) caracterizar el autoarchivo en repositorios institucionales nacionales e internacionales; y c) investigar la consistencia de la indexación de Tesis y Disertaciones de RI/UFSCar aplicando la evaluación de indexación en el enfoque de evaluación intrínseca cualitativa. Es una investigación exploratoria y descriptiva, que tiene como método la investigación bibliográfica con el objetivo de realizar un análisis cualitativo. Los resultados muestran un acuerdo entre los índices evaluados, siendo la indexación del usuario más exhaustiva, pero sin la misma precisión que la indexación realizada por el bibliotecario experto. Como alternativa a la falta de precisión de los términos, existe la disponibilidad de lenguajes documentales para el acceso y uso por parte de los autores / investigadores como referencia para la atribución de términos, la validación de los metadatos de los sujetos por parte de los bibliotecarios y la elaboración de políticas de indización. Para mejorar la representación y recuperación por sujetos en repositorios institucionales.
Self-archiving and subject representation: analytical study of theses and dissertations of the UFSCar Institutional Repository
Autoarchivo y representación temática: estudio analítico de tesis y disertaciones del Depósito Institucional UFSCar
Keywords: Consistência da indexação; Autoarquivamento; Teses e Dissertações; Indexação por extração; Repositórios Institucionais; Consistency in indexing; Institutional repositories; Self-archiving; Institutional Repository of the Universidade Federal de São Carlos; Repositorios institucionales; Autoarchivo; Indización; Consistencia em la indización; Teses y Disertaciones; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::TEORIA DA INFORMACAO::REPRESENTACAO DA INFORMACAO